Making CO₂ a Resource (Taylor & Francis, 2025)
This interdisciplinary book explores how CO2 can become a resource instead of a waste and, as such, be a tool to meet one of the grandest challenges humanity is facing: climate change. Drawing on a Norwegian narrative that has significance for a global audience, Øyvind Stokke and Elin Oftedal introduce in-depth, multi-perspective analyses of a sustainable innovation research experiment in industrial carbon capture and utilisation technologies. Building on extensive literature within marine sciences, sustainability research, and environmental philosophy and ethics, this book documents how a misplaced resource like CO2 can become valuable within a circular economy in its own right, while at the same time meeting the challenge of food security in a world where food production is increasingly under pressure. The book is diverse in scope and includes chapters on how to reduce the environmental footprint of aquaculture by replacing wild fish and soy from the Amazon, how to optimise the monitoring of aquatic environments via smart technologies, and how to replace materials otherwise sourced from natural environments. The authors also analyse the pivotal role of the university in driving innovation and entrepreneurship, the pitfalls of different carbon technologies, and explore how the link between petroleum dependence and CO2 emissions has been addressed in Norway specifically. Making CO2 a Resource will be of great interest to students and scholars of climate change, environmental ethics, environmental philosophy, sustainable business and innovation, and sustainable development more broadly.